Compressive strength versus curing time in hydraulic concrete from modified cements - Rodríguez Rojas, Einer (2025)
This paper presents a synthesis of the experimental results obtained from testing the evolution of the compressive strength in concrete made with different modified cements at different ages. It includes the characterization of two aggregates of different provenances (river and quarry) and three types of modified cements. The cements tested correspond to MM/C (P-C) -28, MM/C (C-P) -28 and MC/A - AR. The objective of the study was to generate the standard resistance development curves of six concrete mixtures (in percentage terms), using these cements and aggregates. The characterization tests were conducted out following the INTECO and ASTM standards. The curing of concrete specimens took place in a humid chamber at 4 different ages (3, 7, 28 and 56 days). The strength of the concrete was obtained through tests on the Universal Machine, and the results were processed and validated statistically, using the acceptance parameters of the ACI 214-2002 report. From the analysis, it was possible to generate the curves of standard development of resistance for all the cements under study using two provenances of aggregates, including an inferential statistical analysis for the resistance results of the concretes. It was concluded that, by varying the origin of the aggregate for the same cement, the resistance of the concrete is significantly different (on statistical terms), as for the same aggregate when the type of cement is changed.